2019
DOI: 10.1097/brs.0000000000002932
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Patients With Undifferentiated High Grade Pleomorphic Sarcoma of the Spine

Abstract: Study Design. Retrospective survival analysis of 44 undifferentiated high grade pleomorphic sarcoma (UPS) of the spine. Objective. To identify factors related to overall survival (OS) and help decision making in the treatment of undifferentiated high grade pleomorphic sarcoma of the spine. Summary of Background Data. UPS is an aggressive malignant tumor rarely originating from the spine. Due to its scarcity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Primary UPS arising from the bone is relatively rare. The statistics have shown that skeletal involvement of UPS represents less than 2% of primary malignant bone tumors [3]. In most cases, UPS of the bone develops around knee joints and in proximal femurs and humerus [3,14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Primary UPS arising from the bone is relatively rare. The statistics have shown that skeletal involvement of UPS represents less than 2% of primary malignant bone tumors [3]. In most cases, UPS of the bone develops around knee joints and in proximal femurs and humerus [3,14].…”
Section: Discussionmentioning
confidence: 99%
“…The statistics have shown that skeletal involvement of UPS represents less than 2% of primary malignant bone tumors [3]. In most cases, UPS of the bone develops around knee joints and in proximal femurs and humerus [3,14]. Only a small number of UPS cases involving the spine have been reported since its rst description in 1975.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations